Study of Socio Economic Conditions of Workers in Spinning Mills in Bhilwara (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The socioeconomic situations of spinning mill workers in Bhilwara, a significant textile centre in Rajasthan, India, are investigated in this research. The study's overarching goal is to shine light on these employees' living situations, incomes, and working circumstances. Data were gathered using a mixed-methods strategy, with a sample of employees from several spinning mills in the area being interviewed and surveyed in an organised manner. Qualitative research centred on recurring themes from the interviews, including work happiness, health worries, and perspectives of social support, whereas quantitative analysis employed descriptive data to show demographic traits, income distribution, and access to fundamental facilities. According to the results, a varied workforce is dealing with a number of socioeconomic issues, such as low salaries, excessive working hours, insufficient healthcare, and few educational chances. Despite these obstacles, the report emphasises that workers are resilient and have a strong sense of community. We address the policy actions that could be necessary to improve the socio-economic circumstances of Bhilwara's spinning mill workers in light of these results. Efforts to improve the lives and rights of textile industry workers are informed by this study, which adds to our knowledge of their experiences on the job.